Benthic Foraminiferal Biostratigraphy of the Tertiary Sediments from the Elazig and Malatya Basins, Eastern Turkey - Caglar (Kaya), Meral (Springer India, 2009)
Tertiary sequences in the Elazig and Malatya Basins, eastern part of Taurus Orogenic Belt, are investigated with the aim of defining the benthic foraminiferal biozones. Tertiary geological units from bottom to top are as follows: Basement rocks, Zorban Formation, Yildiztepe Formation, Suludere Formation, Gedik Formation ( Malatya Basin); Elazig Magmatics, Keban Metamorphics, Harami Formation, Kuscular Formation, Seske Formation, Kirkgecit Formation ( Elazig Basin). Middle-Upper Eocene Yildiztepe, Suludere and Gedik Formations; Upper Paleocene-Lower Eocene Seske Formation and Middle-Upper Eocene Kirkgecit Formation are all characterized by interbedded clastics and carbonate rocks. Six stratigraphic sections are studied in detail for foraminiferal biostratigraphy. Eight benthic foraminiferal biozones are reported. These are; Coskinolina rajkae biozone in the Late Paleocene (Thanetian), Assilina yvettae, Idalina sinjarica biozones in the Late Paleocene; Asterocyclina alticostata gallica biozone in the Early Eocene ( Late Cuisian), Nummulites millecaput biozone in the Middle Eocene ( Middle Lutetian), Nummulites aturicus biozone in the Middle Eocene ( Late Lutetian), Nummulites perforatus biozone in the Middle Eocene (Bartonian), Nummulites fabianii biozone in the Late Eocene (Priabonian). Some key taxa are illustrated.
Keywords: Tertiary; Benthic foraminifera; Biostratigraphy; Malatya Basin; Elazig Basin; Eastern Turkey